Why Muslims Lag Behind Their Western Counterparts - Suryana, A'an (Muslim Politics Review, 2022)
Reopening Muslim Minds: A Return to Reason, Freedom, and Tolerance. Mustafa Akyol. St. Martin’s Essentials (2021) This book explains why Muslims lag behind their Western counterparts, arguing that Muslim backwardness is due to deep-seated religious discourses that are detrimental to Muslim progress. These adverse discourses, such as anti-science stances, narrow views on jihad, and ongoing discrimination against women, are prevalent in many Muslim countries because they are sustained not only by religious authorities but also political ones. This results in mainstream practices of Islam that hinder development, such as the failure of Muslim societies in promoting common sense and reason that are crucial in spurring, for example, social and economic innovations that support progress.